Characterization of genetic elements up-regulated in Pseudomonas aeruginosa PAO biofilms and transcriptional activity of the flagellar hook protein gene, flgE, during biofilm development - Theron, Jacques (University of Pretoria, 2013)
Dissertation (MSc (Microbiology))--University of Pretoria, 2008.